Profil struma non toksik pada pasien di RSUP Prof. Dr. R. D. Kandou Manado periode Juli 2014-Juni 2016 - Tallane, Sarah; Monoarfa, Alwin; Wowiling, P. A.V. (e-CliniC, 2016)
Abstract: Struma or goiter is the most widely thyroid gland disease in the world that causes enlargement of the thyroid gland. This disease can be classified based on clinical, physiological, and anatomical alteration. If the function of the thyroid gland is normal it is called as non-toxic struma that involves many risk factors. This was a descriptive retrospective study using the medical records of all non-toxic struma patients hospitalized at Prof. Dr. R. D. Kandou Hospital Manado from July 2014 to June 2016. There were 38 non-toxic struma patients in this study distributed based on sex, age, morphology, sosioeconomy, region of residences, laboratory results, and therapy. Conclusion: The majority of the patients were females, aged 41-50 years old, diagnosed as non-toxic uninodular struma, middle to low class of socio-economy, living in lowland areas, laboratory result as euthyroid, and treated with surgery.Keywords: struma, enlargement of the thyroid gland, normalÂ Abstrak: Struma (goiter) merupakan penyakit kelenjar tiroid terbanyak di dunia yang menyebabkan pembesaran kelenjar tiroid. Penyakit ini dapat diklasifikasikan berdasarkan klinis, fisiologi, dan perubahan anatomi. Bila kerja kelenjar tiroid normal maka disebut struma non toksik dan melibatkan berbagai faktor risiko. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data rekam medik semua pasien rawat inap struma non toksik di RSUP Prof. Dr. R. D. Kandou Manado periode Juli 2014-Juni 2016. Terdapat 38 pasien struma non toksik yang didistribusi berdasarkan jenis kelamin, usia, perubahan anatomi, sosioekonomi, daerah tempat tinggal, hasil laboratorium, dan terapi. Simpulan: Majoritas pasien terdiri dari perempuan, usia 41-50 tahun, diagnosis struma non-toksik uninodusa, golongan ekonomi menengah ke bawah, tempat tinggal di dataran rendah, hasil pemeriksaan laboratorium cenderung eutiroid, dan terapi tindakan operatif. Kata kunci: struma, pembesaran kelenjar tiroid, normal.